Correction to what drives the redox properties of model green fluorescence protein chromophores? - Solntsev, Kyril M.; Ghosh, Debashree; Amador, Adrian; Josowicz, Mira; Krylov, Anna I. (Journal of Physical Chemistry Letters, 2011)
We report the first experimental determination of the oxidation potentials E-ox(0). (relative to the standard hydrogen electrode, SHE) of model green fluorescent protein (GFP) chromophores. Para-, meta, and ortho-hydroxy (4-hydroxybenzylidene-2,3-dimethylimidazolinone, HBDI) and methoxy (MeOBDI) derivatives were studied. E-ox(0) of the three isomers in acetonitrile are -1.31, -1.52, and -1.39 V, respectively. Electronic structure calculations reproduce the observed differences between the isomers and reveal that E-ox(0) follows the ionization energies (IEs), that is, p-MeOBDI has the lowest IE (6.96 eV in the gas phase) due to resonance stabilization of its cation, whereas the resonance is detuned in m-MeOBDL resulting in more-negative E-ox(0). The observed meta and ortho effects in E-ox(0) are similar to the trends in pK(a). The effect of increased solvent polarity on absolute.E-ox(0) (and especially on para-meta-ortho differences) was found to be small. The redox properties of GFP chromophores are driven by their structure and can be correlated with IEs, which can be exploited in predicting the properties of other fluorescent protein chromophores.